In vitro characterization of phythora palmivora butler isolated from pod rot-infected cacao (theobroma cacao) - Comaradang, Asmin Macadupang (2009)
Phytophthora palmivora Butler was isolated from fruit rot-infected cacao (Theobroma cacao). Pathogenicity test confirmed the association of the microorganism to the disease. On carrot agar medium, the isolate manifested a felted to appressed mycelium forming a stellate colony growth. The caducous, papillate sporangia had a mean length of 58.69 10.13m, and breadth of 35.79 6.75m, papilla length and breadth, respectively, of 5.90 1.45m and 7.20 1.97m, and an average pedicel length of 3.6 1.67m. the chlamydospores were globose with a mean diameter of 33.90 5.67m. the coenocytic hyphae had a mean width of 6.22 0.74m. Colony growth in pH 6 to 8 were almost the same, but cultures ad pH 7 showed the highest spore count. Cultures under continuous light had the biggest colony growth and number of spores than cultures under conditions of alternating 12-hr light: 12-hr darkness and continuous darkness. Cultures under daytime temperatures of 27 2oC had bigger colony growth and produced more spores than cultures incubated temperatures of 22 20C
Thesis (BS Biology) -- University of the Philippines Mindanao, 2009
Keywords: Fruit rot; Cacao -- Varietie; Cacao; Cacao -- Origin and distribution; Cacao -- Ecology; Cacao -- Propagation; Cacao -- Production; Cacao -- Uses; Inoculum; Inoculation; Reisolation; Cacao -- Safekeeping; Cacao -- Storage of cultures; Cacao fruits